Bulbophyllum linzhiense (Orchidaceae, Malaxideae), a new species from China - Ma, Liang; Zhang, Sai; Zhou, Zhuang; Lan, Si-Ren; Chen, Shi-Pin (Phytotaxa, 2020)
We have described and illustrated a new species, Bulbophyllum linzhiense (Malaxideae, Epidendroideae, Orchidaceae), from Tibet Autonomous Region in southwest China. The size and overall floral morphology of the new species are similar to those of B. rubrolabellum, a species endemic to Taiwan island on the southeast coast of China, but is different by apart pseudobulbs, lower flowers, ovate-lanceolate bracts, longer pedicel and ovary, yellow-green flower, and lanceolate lateral sepals. A cladistic analysis based on the nuclear (ITS) and plastid (matK, trnL-F, and atpI-atpH) DNA sequences supported the new species is sister to B. rubrolabellum.